Determinants of Audit Quality in Indonesia - Nuryani, Nanik; Harnovinsah, Harnovinsah; Djaddang, Syahril (Magister Akuntansi Universitas Pancasila, 2025)
Purpose: This study examines the extent of the influence of Public Accountant competence, Audit tenure, audit planning, audit client complexity, auditor competence, engagement quality control, and Public Accounting Firm size on audit quality. Methodology: This research uses quantitative methods using secondary data from examination results conducted by Finance Professions Supervisory Center of The Ministry of Finance, Public Accountant Office business activity reports, and Public Accountant PPL Realization Reports. The research samples were 248 Public Accountants for examination from 2019 to 2023. Finding: The results obtained significant results on the effect of Public Accounting Firms' size on audit quality. In addition, the size of public accounting firms also partially moderates the impact of audit planning on audit quality. The variables of public accountants' competence, audit tenure, audit planning, audit client complexity, auditor competence, and engagement quality control do not affect audit quality. Implication: The implications of these findings suggest that the size of the Public Accounting Firm plays a key role in improving audit quality, making it important for stakeholders to consider the capacity and resources of the Public Accounting Firm in audit assignments. Originality: The originality of this study lies in the simultaneous analysis of the influence of various internal and external factors of the auditor, including moderation of KAP size, on audit quality using real audit data from the financial profession supervisory authority.